2018
DOI: 10.18632/oncotarget.26426
|View full text |Cite
|
Sign up to set email alerts
|

Time to progression to castration-resistant prostate cancer after commencing combined androgen blockade for advanced hormone-sensitive prostate cancer

Abstract: PurposeThe aim of our retrospective study was to determine the time to progression to castration-resistant prostate cancer (CRPC) in prostate cancer patients who undergo combined androgen blockade (CAB), as well as their prognoses.Materials and MethodsWe examined the overall survival (OS) and disease-specific survival rates, as well as the time to CRPC development, in 387 patients who were treated with CAB for prostate cancer. The disease-specific survival rate and time to CRPC were stratified by prostate-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
4
22
1
Order By: Relevance
“…Additionally, several studies aimed to investigate risk factors for progression to mCRPC in mHSPC patients. Several risk factors such as PSA, Gleason score, or time to PSA nadir in mHSPC treatment were found to be such predictors (21)(22)(23)(24)(25)(26). Despite non-significant differences between the four examined TTCR subgroups, possibly due to sample size limitations, we also found interesting trends.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, several studies aimed to investigate risk factors for progression to mCRPC in mHSPC patients. Several risk factors such as PSA, Gleason score, or time to PSA nadir in mHSPC treatment were found to be such predictors (21)(22)(23)(24)(25)(26). Despite non-significant differences between the four examined TTCR subgroups, possibly due to sample size limitations, we also found interesting trends.…”
Section: Discussionmentioning
confidence: 53%
“…We identified that the observation intervals (red area in Figure 5) suggested by our algorithms covered the first 5 years mostly considered by the current clinical guidelines and the follow-up plan practices 23 . Further, our approach has covered the time beyond 5 years where we do not have data from studies on the optimal observation management for urologic cancer diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Internal validation of the model was performed by comparing our estimated total prevalence of the PC cases in Italy in 2018 to the AIOM-AIRTUM data [6]. Various studies provided information on the probability of transition from a clinical stage to another one, or to death [16][17][18][19][20][21][22][23]. These are reported, together with the corresponding probabilities, in Table 1.…”
Section: Methodsmentioning
confidence: 99%